Unveiling the Regulatory Landscape of Stem Cells in India: Assessing Challenges and Opportunities - Rahi Samuel Alhat (International Journal of Medical Toxicology and Legal Medicine, 2024)
The significance of stem cell technology continued in the Indian medical field with the release of the 2019 revised national guidelines on stem cell research. Strict guidelines were enforced by the Department of Biotechnology (DBT) and the Indian Council of Medical Research (ICMR), mandating that stem cell therapy be carried out within the parameters of clinical trials. The ethical and legal implications of stem cell research persisted, particularly in relation to the killing of human embryos in order to harvest embryonic stem cells for study and medical use. Religions from Judaism and Islam support this ethical argument, whereas Buddhism and Hinduism are against it. The ethical standing of embryos and the legal framework controlling stem cell research in India are examined in this article.